Interventions in sexual and reproductive health services addressing violence against women in low-income and middle-income countries: a mixed-methods systematic review. Issue 2 (22nd February 2022) - Lewis, Natalia V; Munas, Muzrif; Colombini, Manuela; d'Oliveira, A F; Pereira, Stephanie; Shrestha, Satya; Rajapakse, Thilini; Shaheen, Amira; Rishal, Poonam; Alkaiyat, Abdulsalam; Richards, Alison; Garcia-Moreno, Claudia M; et al.
Abstract : Objectives: To synthesise evidence on the effectiveness, cost-effectiveness and barriers to responding to violence against women (VAW) in sexual and reproductive health (SRH) services in low/middle-income countries (LMICs). Design: Mixed-methods systematic review. Data sources: Medline, Embase, Psycinfo, Cochrane, Cinahl, IMEMR, Web of Science, Popline, Lilacs, WHO RHL, ClinicalTrials.gov, Google, Google Scholar, websites of key organisations through December 2019. Eligibility criteria: Studies of any design that evaluated VAW interventions in SRH services in LMICs. Data extraction and synthesis: Concurrent narrative quantitative and thematic qualitative syntheses, integration through line of argument and mapping onto a logic model. Two reviewers extracted data and appraised quality. Results: 26 studies of varied interventions using heterogeneous outcomes. Of ten interventions that strengthened health systems capacity to respond to VAW during routine SRH consultation, three reported no harm and reduction in some types of violence. Of nine interventions that strengthened health systems and communities' capacity to respond to VAW, three reported conflicting effects on re-exposure to some types of VAW and mixed effect on SRH. The interventions increased identification of VAW but had no effect on the provision (75%–100%) and uptake (0.6%–53%) of referrals to VAW services. Of seven psychosocial interventions in addition to SRH consultation that strengthened women's readiness to address VAW, four reduced re-exposure to some types of VAW and improved health. Factors that disrupted the pathway to better outcomes included accepting attitudes towards VAW, fear of consequences and limited readiness of the society, health systems and individuals. No study evaluated cost-effectiveness. Conclusions: Some VAW interventions in SRH services reduced re-exposure to some types of VAW and improved some health outcomes in single studies. Future interventions should strengthen capacity to address VAW across health systems, communities and individual women. First-line support should be better tailored to women's needs and expectations. PROSPERO registration number: CRD42019137167.